Heavy menstrual bleeding. (September 2014) - Gupta, Janesh
Janesh Gupta speaks to Caroline Telfer, Commissioning Editor I qualified from University of Leeds, UK in 1987. When I was a 4th year medical student I decided to pursue Obstetrics and Gynecology (O&G) as a career because it involved dealing with women who are going through a happy time in their life, having babies which is a physiological part of life. O&G is a fast-acting specialty which is a combination of medicine and surgery, which led me into this career. After Leeds, I went to Dundee, Scotland as a Senior Registrar, then moving to Birmingham, UK in 1998 as a Senior Lecturer and then getting my Chair as Professor of Obstetrics and Gynecology in 2006.